2015
DOI: 10.1002/ajmg.a.37206
|View full text |Cite
|
Sign up to set email alerts
|

Targeted gene capture and massively parallel sequencing identify TMC1 as the causative gene in a six‐generation Chinese family with autosomal dominant hearing loss

Abstract: Hereditary nonsyndromic hearing loss is extremely heterogeneous. Mutations in the transmembrane channel-like gene1 (TMC1) are known to cause autosomal dominant and recessive forms of nonsyndromic hearing loss linked to the loci of DFNA36 and DFNB7/11, respectively. We characterized a six-generation Chinese family (5315) with progressive, postlingual autosomal dominant nonsyndromic hearing loss (ADNSHL). By combining targeted capture of 82 known deafness genes, next-generation sequencing and bioinformatic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…For the four TMC1 dominant variants, c.1714G>A (p.D572N) and c.1714G>C (p.D572H) affect the same nucleotide, which is proposed to be a recurrent site of variants. The c.1714G>A detected in Family 02 is a known and common dominant variant, accounting for approximately 4.4% (3/68) of ADNSHL in the Chinese population (Gao et al., ). The c.1714G>A variant is located within a cytoplasmic loop between TM4 and TM5 that may play a critical role in forming the pore subunit of the transduction channel (Gao et al., ; Hilgert et al., ; Kurima et al., ; Labay, Weichert, Makishima, & Griffith, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the four TMC1 dominant variants, c.1714G>A (p.D572N) and c.1714G>C (p.D572H) affect the same nucleotide, which is proposed to be a recurrent site of variants. The c.1714G>A detected in Family 02 is a known and common dominant variant, accounting for approximately 4.4% (3/68) of ADNSHL in the Chinese population (Gao et al., ). The c.1714G>A variant is located within a cytoplasmic loop between TM4 and TM5 that may play a critical role in forming the pore subunit of the transduction channel (Gao et al., ; Hilgert et al., ; Kurima et al., ; Labay, Weichert, Makishima, & Griffith, ).…”
Section: Discussionmentioning
confidence: 99%
“…The c.1714G>A detected in Family 02 is a known and common dominant variant, accounting for approximately 4.4% (3/68) of ADNSHL in the Chinese population (Gao et al., ). The c.1714G>A variant is located within a cytoplasmic loop between TM4 and TM5 that may play a critical role in forming the pore subunit of the transduction channel (Gao et al., ; Hilgert et al., ; Kurima et al., ; Labay, Weichert, Makishima, & Griffith, ). The c.1253T>A variant identified in Family 01 is another well‐known dominant TMC1 variant, which has been reported by our group previously; this is the second report of this variant worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In deafness pedigrees, variants affecting protein function in 12 genes were verified with the positive diagnostic rate 56.67% (17/30) ( Table 3). Detailed information on these deafness pedigrees is provided in our previous studies [22][23][24][25][26][27][28][29].…”
Section: Positive Diagnostic Rate For Snvsmentioning
confidence: 99%
“…In China, recent studies on TMC1 mutations such as c.589G>A, c.1171C>T (Xue et al, 2013), c.1209G>C (Tao et al, 2013Tao, Xiaoming, Yongchuan, Lei, & Hao, 2013), c.1253T>A (Yali et al, 2014), c.1714G>A (Xue et al, 2015), and c.1979C>T (Jiongjiong et al, 2016) have been reported. All mutations were analyzed by genetic testing of sporadic families without regional specificity.…”
Section: Discussionmentioning
confidence: 99%